2015
DOI: 10.1111/ans.13211
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic resection for malignant liver tumours in the elderly: a systematic review and meta‐analysis

Abstract: Background: The number of elderly patients undergoing hepatic resection for surgical treatment of benign and malignant cancers is increasing. However, there is limited clinical data on the complications and long-term survival rates associated with liver surgery in the elderly patients (≥70 years) versus younger patients for malignant liver conditions. Methods: Six electronic databases were searched for original published studies comparing elderly (≥70) versus younger (<70) cohorts for malignant liver tumours. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 43 publications
(193 reference statements)
0
25
0
Order By: Relevance
“…Another recent meta-analysis combining both CRLM as HCC and other malignant liver tumours showed higher mortality for elderly patients but comparable disease-free survival. As for the different malignancies, these results are difficult to interpret for patients who undergo liver resection for CRLM [14]. Therefore, this meta-analysis analyses both short- and long-term outcomes for patients who undergo liver resection for CRLM, as both outcomes are relevant for careful decision making.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another recent meta-analysis combining both CRLM as HCC and other malignant liver tumours showed higher mortality for elderly patients but comparable disease-free survival. As for the different malignancies, these results are difficult to interpret for patients who undergo liver resection for CRLM [14]. Therefore, this meta-analysis analyses both short- and long-term outcomes for patients who undergo liver resection for CRLM, as both outcomes are relevant for careful decision making.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic reviews and meta-analysis focussed only on short-term outcomes [13] and combined patients for both CRLM and hepatocellular carcinoma (HCC) [14]. As of a different biological behaviour of HCC compared with CRLM and the importance for long-term results in large populations, a meta-analysis for solely CRLM studying both short- and long-term outcomes will add to more careful decision making in elderly patients affected by CRLM.…”
Section: Introductionmentioning
confidence: 99%
“…Significantly higher mortality rates of 4.8% and severe complication rates of 24% were observed, despite lesser resections being performed in the elderly. A recent systematic review and meta‐analysis concluded that liver resection, in patients over 70, was associated with greater mortality and major complications, but that disease‐free survival was equivalent . This paper highlights the issues with meta‐analysis from heterogenous uncontrolled data sets, often compiled from a range of high and low volume units and over a 35‐year period, which is not representative of modern liver surgery.…”
Section: Discussionmentioning
confidence: 98%
“…A recent systematic review and meta-analysis concluded that liver resection, in patients over 70, was associated with greater mortality and major complications, but that disease-free survival was equivalent. 27 This paper highlights the issues with meta-analysis from heterogenous uncontrolled data sets, often compiled from a range of high and low volume units and over a 35-year period, which is not representative of modern liver surgery. Conversely in our current study of older patients (using a methodology lower on the evidence based medicine pyramid) from a high volume centre, a high proportion of major resections and a high proportion of patients receiving neoadjuvant chemotherapy, is externally valid to nearly all centres performing liver resection in Australia and around the world.…”
Section: Discussionmentioning
confidence: 99%
“…In elderly patients, aggressive curative resection might yield the benefit of improving OS similar to that of younger patients. However, some studies reported that hepatic or pulmonary resection yielded higher mortality and complication rates in elderly compared to younger patients [26, 27]. Therefore, the operative indications for distant metastasis must be carefully decided upon in elderly patients with stage IV CRC.…”
Section: Discussionmentioning
confidence: 99%